Evaluasi Hasil Pengawasan Pemilu Tingkat Desa Dalam Meminimalisir Konflik Antar Peserta Pemilihan Kepala Desa Karangren Kecamatan Krejengan Tahun 2022 - Eko Yudianto Yunus (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2023)
Election is a democratic party that is held with the aim of electing a candidate for a leader who will lead a certain area. Village head elections are held every six years. In 2022 Karangren Village, Krejengan District, will carry out election activities which will end up causing various kinds of conflicts. In the election for the head of Karangren Village, 3 candidates for village heads were brought together, namely Abdul Karim as candidate for village head with serial number 1, Subandi with serial number 2, and Yeti Nurhayati with candidate for village head serial number 3. The conflict occurred as a result of strong competition and between the two camps, namely candidate serial number 2 and candidate serial number 3. Which caused many disputes to arise both between the village head candidates and the community as supporters of each village head candidate. So that some of these conflicts led to chaos and made the situation in Karangren Village not conducive. This study aims to find out about the evaluation of the results of election supervision at the village level in an effort to minimize conflict between participants. The method used in this study is a qualitative method with data collection in the form of literature reviews, interviews and observations. The results of the research are that it is known that the conflicts that have occurred have been resolved using persuasive methods by community leaders in Karangren Village.